2011
DOI: 10.1097/dcr.0b013e31821cc1f9
|View full text |Cite
|
Sign up to set email alerts
|

Does Adjuvant Antibiotic Treatment After Drainage of Anorectal Abscess Prevent Development of Anal Fistulas? A Randomized, Placebo-Controlled, Double-Blind, Multicenter Study

Abstract: Antibiotic treatment following the drainage of an anorectal abscess has no protective effect regarding risk of fistula formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 20 publications
1
47
1
6
Order By: Relevance
“…Various factors related to the recurrence of anorectal abscesses such as age, sex, body mass index, onset time of symptoms, diabetes mellitus presence, place and anatomic classification of the abscess, antibiotic use, form of anesthesia and use of drain were investigated (7,12,14). In our study, no correlations could be identified between variables such as age, sex, hospi- (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Various factors related to the recurrence of anorectal abscesses such as age, sex, body mass index, onset time of symptoms, diabetes mellitus presence, place and anatomic classification of the abscess, antibiotic use, form of anesthesia and use of drain were investigated (7,12,14). In our study, no correlations could be identified between variables such as age, sex, hospi- (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Die beschriebenen Arbeiten zeigen, dass nur ein Teil der wegen eines Abszesses Operierten sekundär wegen einer Fistel reoperiert werden musste. Nach Auswertung der Literatur führen lediglich 30% der Abszesse zu einer persistierenden Fistel [54,87,98].…”
Section: Häufigkeit Des Sekundären Fistelnachweisesunclassified
“…Deutlich niedriger war sie nach subanodermalen Abszessen mit 7,3%, nach intersphinkteren Abszessen mit 8,0% und nach ischioanalen Abszessen mit 10,9%. Ähnliche Ergebnisse mit höheren Fistelraten nach ischioanalen und intersphinkteren Abszessen gegenüber der subanodermalen Lokalisation beschreibt auch eine aktuelle Studie [98] [54]. In diesem Zusammenhang ist auf die weltweit zunehmende Resistenzentwicklung durch den unkritischen Einsatz von Antibiotika zu verweisen [49].…”
Section: Häufigkeit Des Sekundären Fistelnachweisesunclassified
See 1 more Smart Citation
“…Ommer et al, 2012 (30) showed that antibiotics should be used in the presence of immunosuppression. A randomized, controlled, multi-center clinical trial study showed that the use of antibiotics could not prevent the development of fistulas after ID of PA (31). Therefore, antibiotics should be combined with surgical measures.…”
Section: Discussionmentioning
confidence: 99%